Ends of the Mahābhārata - Shalom, N (2012)
The assertion that the Mahābhārata (MBh) narrative is innately incapable of achieving a conclusion has attained the status of a disciplinary truism in the epic’s study. My thesis challenges this prevalent assumption by proposing an un-investigated path of inquiry into the philological, historical, literary and semantic aspects of the epic. The thesis discusses the ending of the MBh, the Svargārohaṇa parvan (SĀ) by exploring several trajectories: the study of the SĀ in epic scholarship; its reception in the later tradition in Sanskrit literature; and finally, the problematic aspects of the SĀ and its relation to the rest of the narrative. It first points out that in comparison to other MBh episodes, the SĀ has been received with significant disregard or suppression in the literature commenting on the epic. Second, it characterizes the nature of the suppression of the SĀ in each of the three literary strands commenting on the MBh (epic scholarship, Sanskrit adaptations and theoretical discourses). It argues that all of these considerations, which are external to the MBh, have tended, in various modes, to suppress, ignore or overlook the importance of the SĀ. The thesis then proceeds to argue that on the most significant and internal level of the text itself, the SĀ is intrinsically consistent with the rest of the MBh narrative, and that this makes it thematically integral to the text as a whole. This argument derives from the importance with which this study addresses the moment of the condemnation of dharma in the SĀ, and is furthered by a philological and semantic study, as well as textual analyses of the multiple occurrences of the Sanskrit verb garh throughout the MBh. The use of this verb by the epic protagonist, Yudhiṣṭhira, in condemning his father, Dharma, at the last scenes of the SĀ comprises a key moment that bears significant and myriad implications upon the understanding of this pivotal concept (dharma), to which the entire epic is devoted.